2018
DOI: 10.5539/jel.v7n6p124
|View full text |Cite
|
Sign up to set email alerts
|

Students’ School Engagement and Their Truant Behavior: Do Relationships with Classmates and Teachers Matter?

Abstract: Research on school dropout suggests that the decision to drop out of school is not a sudden or immediate one, but rather the result of a long-term process of withdrawal from school. While school engagement and truancy are among the most prominent constructs to be associated as precursors of school dropout, the relationship between these two constructs needs further analysis. Our study establishes more comprehensive understanding of school engagement and truancy by focusing on students’ individual cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…Dreeben (1968) pointed out that not all pupils have the cognitive resources and the social support that lead to the acceptance and adoption of the universalistic-specific norms expected in schools. Accordingly, some studies indicate that particularly at-risk pupils -pupils from disadvantaged and/or immigrant backgrounds and pupils with socio-emotional problems -depend more than other pupils on caring pupil-teacher relationships and socio-emotional support (Tardy, 1985;Tennant et al, 2015;Teuscher & Makarova, 2018). A further factor is that immigrant pupils may come from cultural backgrounds that place a higher value on collectivistic norms and therefore more easily come into conflict with the norms of independence and universalism in schools (Raeff et al, 2000;Rothstein-Fisch et al, 2009).…”
Section: Institutional Demands Learner Needs and Teacher Strategiesmentioning
confidence: 99%
“…Dreeben (1968) pointed out that not all pupils have the cognitive resources and the social support that lead to the acceptance and adoption of the universalistic-specific norms expected in schools. Accordingly, some studies indicate that particularly at-risk pupils -pupils from disadvantaged and/or immigrant backgrounds and pupils with socio-emotional problems -depend more than other pupils on caring pupil-teacher relationships and socio-emotional support (Tardy, 1985;Tennant et al, 2015;Teuscher & Makarova, 2018). A further factor is that immigrant pupils may come from cultural backgrounds that place a higher value on collectivistic norms and therefore more easily come into conflict with the norms of independence and universalism in schools (Raeff et al, 2000;Rothstein-Fisch et al, 2009).…”
Section: Institutional Demands Learner Needs and Teacher Strategiesmentioning
confidence: 99%
“…No significant gender differences were observed in our sample. Although some previous studies reported gender effects in school engagement [38, 42], other studies do not [43, 44, 45], yet most studies do not report statistics on gender differences (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although empirical evidence connecting student engagement and truancy is scarce (Teuscher & Makarova, 2018), existing evidence has shown that, in general, the levels of students’ participation at and identification with school are of the utmost importance for their behavioral and psychological outcomes, including school dropout, delinquency, substance use, mental health, educational aspirations, academic achievement, and college enrollment rates (e.g., Li & Lerner, 2011; Wang & Fredricks, 2014; Wang & Peck, 2013). Cross-sectional studies have indicated a negative correlation between the effort students exert in doing their schoolwork, paying attention in class, and preparing for classes and school truancy (Virtanen et al, 2014).…”
Section: Participation-identification Modelmentioning
confidence: 99%
“…Cross-sectional studies have indicated a negative correlation between the effort students exert in doing their schoolwork, paying attention in class, and preparing for classes and school truancy (Virtanen et al, 2014). Teuscher and Makarova (2018) showed that after controlling for students’ sex, age, grades, relationships with peers, relationships with teachers, and family’s migration and socioeconomic background, the negative correlation between students’ combined behavioral, cognitive, and affective engagement and truancy was moderate to large (Cohen, 1988). Vaughn et al (2013) showed that in comparison with nontruant youths, students with truant behavior reported attending fewer school activities, had lower levels of liking school, and found schoolwork less meaningful, interesting, and important.…”
Section: Participation-identification Modelmentioning
confidence: 99%